Molecular Evidence Of Phytohormonal Modulatory Effect Of Serratia Liquefaciens On Rice (Applied Biological Research, 2020)
The potential plant growth promoting rhizobacterium Serratia liquefaciens isolate KM2 (SL-KM2) was evaluated for its effect on the growth and  hormonal homeostatic in rice cv. ‘Dandi’. The rice seeds were treated with  SL-KM2 and sown in po;ybags. The phytohormonal analysis of rice  seedlings was performed 20 days after sowing (DAS) by using UFLC  techniques. The study showed that SL-KM2 seed treatment balanced  phytohormones homeostatic wherein gibberellic acid (GA3) and indole  acetic acid (IAA) contents in leaves and root tissues were affected positively whereas abscisic acid (ABA) and jasmonic acid (JA) were negatively  affected. The balanced phytohormone contents resulted in improvement in  physiological parameters viz., root length, root volume, shoot length and  fresh weight as compared to the untreated control. The expression analysis  of genes involved in phytohormones perceptionand signaling was  performed by qRT-PCR technique at 20 DAS which furtherconfirmed seed  treatment-mediated hormonal modulation. Under seed treatment condition, the genes GAI1, EIL1, PR1, PAL, EDS1 and AOS2 were up-regulated in leaf tissue whereas ERF1 gene was down-regulated. In case of root tissue, genes  GAI1, EIL1, ERF1, PAL and EDS1 were up-regulated whereas genes PR1 and AOS2 were down-regulated. Besides improving the seedling physiology,  the up-regulation of PAL and PR1 by SL-KM2 seed treatment imparted  better stress tolerance in plant. This study confirms the association of  phytohormone-related gene expression with observed hormonal state  contributing toward enhanced physiological response in rice.
Keywords: Gene expression analysis; PGPR traits,; phytohormones; rice; Serratia liquefaciens